Antioxidant Activity, Phenol And Flavonoid Content Of Some Less Known Medicinal Plants Of Assam - L.R.SAIKIA; SRISTISRI UPADHYAYA (International Journal of Pharma and Bio Sciences, 2011)
Ethanolic extract of four medicinal plants Polygonum microcephalum, Moringa oleifera, Croton tiglium and Gomphrena globosa were examined for antioxidant activity, and phenol and flavonoid content. Total phenol and flavonoid content and DPPH radical scavenging activity of the extracts were spectrophotometrically determined. Catechol, Quercetin, and ascorbic acid were taken as standard in case of phenol, flavonoid content and antioxidant activity respectively. The total phenol and total flavonoid content was observed highest in P. microcephalum. The DPPH radical scavenging activity was highest in M. oleifera. There observed a relationship between phenol and flavonoid content but failed to show relationship between phenolic content and antioxidant activity of the ethanol extracts of the plants.